Contesting Expertise in Prison Law - Kerr, Lisa (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2014)
Prisons present a special context for the interpretation of constitutional rights, where prisoner complaints are pitched against the justifications of prison administrators. In the United States, the history of prisoner rights can be told as a story of the ebb and flow of judicial willingness to defer to the expertise-infused claims of prison administrators. Deference is ostensibly justified by a judicial worry that prison administrators possess specialized knowledge and navigate unique risks, beyond the purview of courts. In recent years, expansive judicial deference in the face of “correctional expertise” has eroded the scope and viability of prisoners’ rights, serving to restore elements of the historical category of “civil death” to the legal conception of the American prisoner. In Canada too, courts have often articulated standards of extreme deference to prison administrators, both before and after the advent of the Charter of Rights and Freedoms, and notwithstanding that the Charter places a burden on government to justify any infringement of rights. Recently, however, two cases from the Supreme Court of British Columbia mark a break from excessive deference and signify the (late) arrival of a Charter-based prison jurisprudence. In each case, prisoner success depended on expert evidence that challenged the assertions and presumed expertise of institutional defendants. In order to prove a rights infringement and avoid justification under section 1, the evidence must illuminate and specify the effects of penal techniques and policies on both prisoners and third parties. The litigation must interrogate the internal penal world, including presumptions about the workings of prisoner society and conceptions of risk management.